MOTIVASI PENGUNJUNG PADA OBJEK WISATA TAMAN BUNGA IMPIAN OKURA KOTA PEKANBARU - Nova, Aulia; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Indonesia is a rich country because it has attractions offered through the uniqueness of its culture and the attractions of its tourist attractions. The natural beauty makes Indonesia a country that maintains its great potential in the tourism sector, one of which is Pekanbaru City in Riau Province. There are several reasons that influence the motivation for tourist trips, including: the first reason is education, the second is entertainment, the third is health, the fourth is business. This study aims to find out what motivates tourists who visit Okura Dream Flower Park. This study uses a qualitative method by collecting specific data from the field. This study uses data collection techniques from observation, interviews, and documentation. The results of this study can be seen that Okura Dream Flower Park is a flower-themed tourist attraction in Pekanbaru City. Keywords: Motivation, Visitors